1997
DOI: 10.1074/jbc.272.52.33435
|View full text |Cite
|
Sign up to set email alerts
|

p300 Functions as a Coactivator for the Peroxisome Proliferator-activated Receptor α

Abstract: The integrator protein, p300, was demonstrated to interact with mouse peroxisome proliferator-activated receptor ␣ in a ligand-enhanced manner. The PPAR␣-interacting domain of p300 was mapped to amino acids 39 -117 which interacted strongly with PPAR␣ but did not interact with retinoic acid receptor-␥ or retinoid X receptor-␣. Amino acids within the carboxyl terminus of PPAR␣ as well as residues within the hinge region were required for ligand-dependent interaction with p300. p300 enhanced the transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
106
2
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(112 citation statements)
references
References 85 publications
3
106
2
1
Order By: Relevance
“…Furthermore, this ligand-dependent co-activator association suggests that the novel ligands are agonists for either PPAR␥ or PPAR␦. It is worth noting that Dowell et al (33) reported recently that p300 (a homologue of CBP) can function as a co-activator for PPAR␣.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this ligand-dependent co-activator association suggests that the novel ligands are agonists for either PPAR␥ or PPAR␦. It is worth noting that Dowell et al (33) reported recently that p300 (a homologue of CBP) can function as a co-activator for PPAR␣.…”
Section: Resultsmentioning
confidence: 99%
“…GST pull-down assays were as described (38). The GST-Foxo1 fusion protein encoded amino acids 436 -652 of Foxo1 (the Foxo1 region identical to that identified during the twohybrid screen).…”
Section: Methodsmentioning
confidence: 99%
“…HNF4␣ and PPAR␣ engage a multitude of transcriptional coregulators, including the corepressor NCor (Dowell et al 1999), and coactivators such as p300/CBP (Dowell et al 1997), the PPAR␥-coactivators PGC-1␣ and PGC-1␤ (Vega et al 2000), and the Mediator subunit MED1/TRAP220/DRIP205/PBP/CRSP200 (subsequently named MED1) Malik et al 2004). In addition, med1 −/− mouse embryonic fibroblasts fail to properly express many PPAR␥ target genes, and are incapable of undergoing proper adipocyte differentiation, a PPAR␥-dependent cell fate decision (Ge et al 2002).…”
mentioning
confidence: 99%